(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s
(3ChdgG (B:s
(3gPG cJGH MQa GdZjf ef JgPjH GddZI CHhGH GdeVGYa Z b bGd GHf GdeXaQ Jbhd GdYQH Zb GdbOQ jZb ZbjbkG s
(3BNQgG (B:s
(3hbGd GdcSGFi eG MLhJ efg TjFkG hbGd CHh YHjO bGd GdaQGA s
(3HgG WeS TOjO COi Edi fbUGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs